2020
DOI: 10.1128/msphere.00476-20
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Extracellular Vesicles Produced by Aspergillus fumigatus Protoplasts

Abstract: Extracellular vesicles (EVs) are membranous compartments produced by yeast and mycelial forms of several fungal species. One of the difficulties in perceiving the role of EVs during the fungal life, and particularly in cell wall biogenesis, is caused by the presence of a thick cell wall. One alternative to have better access to these vesicles is to use protoplasts. This approach has been investigated here with Aspergillus fumigatus, one of the most common opportunistic fungal pathogens worldwide. Analysis of r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 79 publications
2
69
0
Order By: Relevance
“…In fungi, EVs are also involved in the transport of macromolecules across the cell wall [113]. Various reports have described the release of EVs by several species of pathogenic fungi in both yeasts and filamentous fungi [114][115][116][117][118][119][120]. Conventional and unconventional secretory pathways have been proposed for the release of EVs by fungi.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…In fungi, EVs are also involved in the transport of macromolecules across the cell wall [113]. Various reports have described the release of EVs by several species of pathogenic fungi in both yeasts and filamentous fungi [114][115][116][117][118][119][120]. Conventional and unconventional secretory pathways have been proposed for the release of EVs by fungi.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…In these organisms, a large body of literature describes how EVs participate in intercellular signaling within and in organism-to-organism communication, including carcinogenesis and host-pathogen interactions (Xu et al 2018, Shopova et al 2020). In fungi, the first report of fungal EVs was published in 2007 (Rodrigues et al 2007), and, since then, their existence has been reported in many species of pathogenic and nonpathogenic fungi (Rizzo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence of C. neoformans surface lipids revealed plasma membrane projections, suggesting that the plasma membrane could bud and release EVs ( Rodrigues et al, 2000 ). The participation of the plasma membrane in fungal EVs formation was also shown using “wall-less” Aspergillus fumigatus cells ( Rizzo et al, 2020a ). Ultra-resolution microscopy analyses of these fungal protoplasts demonstrated the occurrence of EVs budding from the plasma membrane.…”
Section: Cellular Sites and Mechanisms Of Extracellular Vesicle Formation In Fungimentioning
confidence: 85%
“…In addition, the deletion of the sterol biosynthesis gene Erg6 induced changes in the lipid and protein content of C. neoformans EVs, suggesting a role for sterols in EVs formation ( Oliveira et al, 2020 ). Studies have shown that fungal EVs can originate from intracellular organelles, such as endosomes ( Oliveira et al, 2010 ; Zarnowski et al, 2018 ; Zhao et al, 2019 ; Park et al, 2020 ), or at the plasma membrane ( Rodrigues et al, 2000 , 2013 ; Rizzo et al, 2020a ). Morphological studies of C. neoformans showed structures resembling multivesicular bodies (MBVs) that can fuse to the plasma membrane, resulting in the release of intraluminal MBV vesicles into the fungal periplasm ( Takeo et al, 1973 ).…”
Section: Cellular Sites and Mechanisms Of Extracellular Vesicle Formation In Fungimentioning
confidence: 99%
See 1 more Smart Citation